Melodinus eugeniifolius. (apocynaceae juss.): a phytochemical and pharmacological study - Lu, Yao (2016)
Melodinus eugeniifolius. a very rare medicinal plant belongs to the family of Apocynaceae. This family consists of 424 genera and 1,500 species of trees. In the Asia-Pacific region, about 20 species of Apocynaceae are used to treat various diseases like cancer, cardiovascular diseases and infectious diseases. Furthermore, almost no pharmacological and phytochemical studies in genera Melodinus, no pharmacological and phytochemical studies in this plant as well. This study was undertaken to screen the phytochemical and phytochemical aspects on the plant Melodinus eugeniifolius.